Extent and potential impact of hunting on migratory shorebirds in the Asia-Pacific. (June 2020) - Gallo-Cajiao, Eduardo; Morrison, Tiffany H.; Woodworth, Bradley K.; Lees, Alexander C.; Naves, Liliana C.; Yong, Ding Li; Choi, Chi-Yeung; Mundkur, Taej; Bird, Jeremy; Jain, Anuj; Klokov, Konstantin; Syroechkovskiy, Evgeny; et al.
Abstract: Harvesting has driven population declines of migratory species. In the East Asian-Australasian Flyway (EAAF), declines of migratory shorebirds have been largely attributed to habitat loss. However, despite concerns about hunting, no study has considered this potential threat at a flyway scale. We synthesised and analysed the current state of knowledge of hunting of migratory shorebirds in the EAAF to determine: (i) whether there is flyway-wide coordination for monitoring hunting; (ii) the temporal, spatial, and taxonomic extent of hunting; and (iii) the potential population-level effects. We conducted an exhaustive literature search, aggregated data considering uncertainty in different dimensions, and appraised hunting levels against sustainable harvest thresholds. We identified 138 references (i.e., peer-reviewed journal articles, book chapters, books, conference proceedings, technical reports, theses, and newsletters) as potential sources of records of hunting of migratory shorebirds of which we were able to obtain 107. We discovered a lack of coordinated monitoring of hunting, despite harvest being temporally, spatially, and taxonomically pervasive, including species of conservation concern. Past harvest levels of migratory shorebirds may have reached at least half of the flyway-wide sustainable thresholds in the EAAF. Despite our inability to assess current hunting levels and unambiguous population-level effects, it is evident that hunting has the potential to be an additional stressor on migratory shorebird populations interplaying with habitat loss. We therefore highlight the need to develop a coordinated monitoring system of hunting at a flyway scale, as past levels of take are likely to have been unsustainable, hunting still occurs, and the current thresholds for sustainable harvest have become lower as a result of declines in shorebird populations. Highlights: Overharvesting is a pervasive threat to biodiversity, yet evaluating it remains challenging. Hunting of migratory shorebirds in the Asia-Pacific remains poorly understood as a threat. We discovered a lack of robust data on hunting, hampering efforts to inform conservation policy. Though based on limited evidence, hunting is potentially a driver of population declines. A regional approach to monitoring hunting is urgently required in the Asia-Pacific.